IDENTIFIKASI INTERIOR PADA BANGUNAN CAGAR BUDAYA DI KOTA BANDUNG (STUDI KASUS : GPIB MARANATHA BANDUNG) - M Rizky Fauzi; Yusuf Satria Wicaksono; Rizky Julian Dewanto; Muhammad Daffa Wafda A; Ardhiana Muhsin (Program Studi Arsitektur Sekolah Tinggi Teknologi Cirebon, 2023)
Cultural heritage is a material cultural heritage inherited from previous generations which is then preserved by the next generation. Bandung is a city that has quite a lot of cultural heritage objects, one of which is a cultural heritage building that needs to be preserved by the community. The process of preserving cultural heritage does not need to produce a new design work, the preservation of cultural heritage buildings can be done with several stages, one of which is identifying architectural historical objects, with a case study of GPIB Maranatha Bandung, a combined qualitative and quantitative method is used in identifying the GPIB Maranatha Bandung building through the following research stages: (a) field observation at the observation location including interviews, measurements and recording as well as related supporting documents (b) identifying and analyzing the details of each exterior element of the building (tower, and terrace) (c) identifying and analyzing the details of each interior element of the building (zoning space, foyer/stair room, worship space, balcony, priest preparation room, openings, ceiling, floor, and other supporting elements.